Multicultural Classroom Management: Strategies for Managing the Diversity of Students in Elementary Schools and Madrasah Ibtidaiyah - Mustafida, Fita (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
A comfortable classroom environment cannot be separated from the role of the teacher in managing the learning environment. Heterogeneous classroom conditions are a challenge for teachers to create a conducive and meaningful learning atmosphere. This is because each student has different characters, needs, and potentials that need to be developed. On the other hand, the heterogeneity of students if not managed properly can be a source of various problems in the classroom. Starting from bullying, the learning atmosphere is uncontrollable, even the attitude of antipathy to diversity triggers other negative attitudes, such as discrimination and injustice. Therefore, to overcome this problem, it requires the ability of teachers to create a classroom environment that respects diversity (multicultural). Based on this view, multicultural class management is needed. This is because multicultural classroom management is believed to be able to foster student diversity while still adhering to universal human values that are just and in favor of equality. Multicultural classroom management is also able to provide educational services that are by human needs, and respect differences with the human approach. On this basis, this study discusses teacher strategies in managing the diversity of students using a multicultural classroom management approach. Multicultural classroom management needs to be developed to create a more humanist and democratic learning atmosphere which is needed to foster the diversity of students in the classroom. Among the multicultural class management strategies that can be carried out are managing gender diversity, social status, ethnicity, including intelligence Â